Enhancing Food Supply Chain Efficiency: A Consolidation Shipping Approach For Multi-Product and Multiechelon: Meningkatkan Efisiensi Rantai Pasokan Pangan: Pendekatan Konsolidasi Pengiriman Untuk Multi-Produk dan Multiechelon - Handayani, Dwi Iryaning; Kurnia Iswardani; Haryono, Haryono; Prihatinigsih, Tri Prihatiningsih (Universitas Muhammadiyah Sidoarjo, 2023)
This research applies the application of delivery consolidation in the context of a multi-product and multi-echelon food supply chain, as a strategy to address operational efficiency and cost management. The aim is to implement consolidation in multi-product and multi-echelon distribution systems, in order to optimize product placement and distribution efficiently. The method adopted is the Linear Programming model, which considers key variables such as the number of goods to be sent, delivery route, resource allocation, fleet capacity and delivery time limit. The research results show that shipment consolidation, by scheduling shipments that are delayed until the second or third day, allows combining orders into one large shipment, thereby increasing load and route efficiency, reducing trip frequency, and achieving significant transportation cost savings. This strategy successfully increased load and route efficiency, reduced the number of trips required, and resulted in substantial transportation cost savings. Using this method, the total shipping and storage costs are 1,328,834. This consolidation strategy has proven crucial in optimizing delivery types, in addition to facilitating more effective route planning, reducing travel distances and times, and resulting in significant operational cost savings.